mSphere of Influence: Translating Gut Microbiome Studies To Benefit Human Health - Anna M. Seekatz (American Society for Microbiology, 2020)
ABSTRACT Anna M. Seekatz works in the field of the gut microbiome as it related to infectious diseases. In this “mSphere of Influence” article, she reflects on how two studies, “The impact of a consortium of fermented milk strains on the gut microbiome of gnotobiotic mice and monozygotic twins” (N. P. McNulty, T. Yatsunenko, A. Hsiao, et al., Sci Transl Med 3:106ra106, 2011) and “High-throughput DNA sequence analysis reveals stable engraftment of gut microbiota following transplantation of previously frozen fecal bacteria” (M. J. Hamilton, A. R. Weingarden, T. Unno, A. Khoruts, and M. J. Sadowsky, Gut Microbes 4:125–135, 2013), shaped how she approaches interpreting microbiome studies.